1998
DOI: 10.1136/bmj.317.7154.321
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing fever by touch: observational study

Abstract: 2 We assessed whether mothers and medical students could use touch to determine if children had fever. Subjects, methods, and resultsDuring their elective in a Zambian hospital, medical students and the child's mother felt children's abdomen, forehead, and neck and independently recorded whether the child felt hot. Simultaneously, a mercury thermometer was used to measure axillary temperature for exactly 3 minutes. Rectal temperature measurement was not permitted at this hospital.In total, 1090 children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
3
10

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 5 publications
0
26
3
10
Order By: Relevance
“…The detection of fever by palpation is an ageold method that is insensitive and less accurate; 15% of caregivers in our study population reported still using this method. A large study by Whybrew et al assessed whether mothers and medical students could use touch to determine if children had fever and found touch to overestimate skin temperature and thus falsely label children as having fever [27]. Since the use of a thermometer is the only way to determine whether a child has a fever and all other tactile and visual assessments are inaccurate, there is a great need for future large population studies to identify more standardized, age-appropriate, noninvasive, and costeffective temperature measurement methods for children.…”
Section: Discussionmentioning
confidence: 99%
“…The detection of fever by palpation is an ageold method that is insensitive and less accurate; 15% of caregivers in our study population reported still using this method. A large study by Whybrew et al assessed whether mothers and medical students could use touch to determine if children had fever and found touch to overestimate skin temperature and thus falsely label children as having fever [27]. Since the use of a thermometer is the only way to determine whether a child has a fever and all other tactile and visual assessments are inaccurate, there is a great need for future large population studies to identify more standardized, age-appropriate, noninvasive, and costeffective temperature measurement methods for children.…”
Section: Discussionmentioning
confidence: 99%
“…To detect fever, touch has a sensitivity of up to 94%, but the aural thermometers favoured by the clinicians surveyed are less sensitive in clinical use, 13,14 probably because of user errors and variations in the external auditory canal. 15 The height of fever has relatively poor sensitivity for identifying serious infection, which may explain responders' wide variation in definitions of fever.…”
mentioning
confidence: 99%
“…4,5,[7][8][9][10][11][12][13] Bununla birlikte annenin dokunarak çocuğundaki ateşi tespit etmedeki başarısı belirsizdir. Bu çalışmalarda duyarlılık %70-%97, seçicilik %19-%90, PPV %38-97, NPV ise %46-98 arasında değişmektedir.…”
Section: Discussionunclassified